Essays in Accounting Theory (Book). - Anton, Hector R.; Caplan, Edwin H.; Stickney, Clyde P.; Brief, Richard P. (The Accounting Review, 1987)
Reviews the book "Essays in Accounting Theory," by Carl T. Devine.